Thermal Tolerance and Prediction of Northern Distribution of the Crapemyrtle Bark Scale (Hemiptera: Eriococcidae). Issue 3 (12th March 2019) - Wang, Zinan; Chen, Yan; Diaz, Rodrigo
Abstract: Physiological limits of non-native species to environmental factors are critical for their establishment and spread in the adventive range. The crapemyrtle bark scale, Acanthococcus lagerstroemiae (Kuwana), is a major pest of crapemyrtles. Despite concerns on its rapid spread, there is a lack of information on potential distribution range of this scale in the United States. To understand this scale's distribution potential, its thermal tolerance was evaluated using higher and lower thermal limits. Exposure time leading to 50 and 90% mortality (Lt50 and Lt90 ) at extreme low or high temperatures were measured under controlled conditions. A model was then built to fit temperature data of cold fronts from 2001 to 2016 and to calculate potential mortalities along latitudes. Isothermal lines delineated at 90% mortality were defined as the northern limits. Modeling results suggested that A. lagerstroemiae nymphs collected in summer could tolerate heat; however, they were more susceptible to cold temperatures. Laboratory assays suggested that cold tolerance of A. lagerstroemiae nymphs varied from summer to winter. For example, SCP of nymphs collected in summer was higher than those collected in fall (−21 vs. −27°C), and the exposure time leading to Lt90 at 0°C was also different, which were 8 versus 50 h comparing nymphs collected in summer versus fall. Our prediction suggested that A. lagerstroemiae is likely to be limited by cold temperatures along the 43° N latitude. Based on these results, integrated management strategies can be developed for A. lagerstroemiae within the predicted range.